2018
DOI: 10.1111/pirs.12237
|View full text |Cite
|
Sign up to set email alerts
|

Institutions vs. 'first‐nature’ geography: What drives economic growth in Europe's regions?

Abstract: The debate on whether institutions or geography prevail in driving economic growth has been rife (e.g., Sachs 2003 vs. Rodrik et al. 2004). Most of the empirical analyses delving into this debate have focused on world countries, whose geographical and institutional conditions differ widely. Subnational analyses considering groups of countries with, in principle, more similar institutional and geographical conditions have been limited and tended to highlight that geography is more important than institutions at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 71 publications
(133 reference statements)
5
68
1
1
Order By: Relevance
“…The coefficient shows that the quality of provincial government has a positive connection with firm's TFP. This result is in line with previous research that focused on the importance of institutions at the sub-national level (Tabellini, 2010;Ketterer & Rodríguez-Pose 2016;Rodríguez-Pose & Di Cataldo, 2014;Lasagni et al, 2015) (Note 13). Specifically for Italy, Lasagni et al (2015) focused on the Institutional Quality Index for Italian provinces and found that local institution quality does matter, as it proves to be one of the main drivers of firm productivity differentials.…”
Section: Individually (Note 8)supporting
confidence: 82%
“…The coefficient shows that the quality of provincial government has a positive connection with firm's TFP. This result is in line with previous research that focused on the importance of institutions at the sub-national level (Tabellini, 2010;Ketterer & Rodríguez-Pose 2016;Rodríguez-Pose & Di Cataldo, 2014;Lasagni et al, 2015) (Note 13). Specifically for Italy, Lasagni et al (2015) focused on the Institutional Quality Index for Italian provinces and found that local institution quality does matter, as it proves to be one of the main drivers of firm productivity differentials.…”
Section: Individually (Note 8)supporting
confidence: 82%
“…Another part of literature has then explained the different roles of institutions on the investment returns by using several explanations. The performance of public institutions has been related to their geographical position [56]. Charron (2016) [57] has advanced the hypothesis that the heterogeneity in Structural Funds distribution to European Union regions depends on the interaction between regional formal institutions (the level of a regional autonomy), and informal institutions (its level of government quality).…”
mentioning
confidence: 99%
“…Finally, following Ketterer and Rodríguez‐Pose (), we control for historical institutional legacies with two variables. The first measures whether a region was part of Charlemagne's empire at his death in the year 814.…”
Section: Discussionmentioning
confidence: 99%
“…Institutional quality is an expansive and nebulous concept and is often used interchangeably with terms such as quality of government and good governance (Charron, Dijkstra, & Lapuente, ; Ketterer & Rodríguez‐Pose, ). The terms usually also encompass the same subindicators, like property rights protection, rule of law, impartiality, absence of corruption, and government effectiveness.…”
mentioning
confidence: 99%